The Aesthetics of Populism: Political Struggle and the Aesthetics Experience in Poland after 1989 - Koczanowicz, Leszek,; Stambulski, Michał,; Ufel, Wojciech,; Włodarczyk, Rafał, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2025)
Do populists and liberal democrats recognizably differ in their lifestyles, clothes, eating habits, or reading preferences? Do the supporters of populism and liberal democracy look at the past from different perspectives? How do their aesthetic choices influence their political engagement? You will find these and similar questions addressed (and answered) by the contributors to this collection. The volume owes its special place in the literature on political aesthetics to its interdisciplinarity. It combines theoretical explorations of the ways aesthetics can be used to analyze political developments and empirical research that comprehensively illuminates the relevance of aesthetics to political struggle.